Multi-generational Effects of Different Resistant Wheat Varieties on Fitness of Sitobion avenae (Hemiptera: Aphididae). Issue 5 (16th October 2021) - Hu, Xiang-Shun; Luo, Chen; Li, Guang-Kuo; Zhang, Zhan-Feng; Wang, Chun-Ping; Hu, Zu-Qing; Zhao, Hui-Yan; Liu, Tong-Xian
Abstract: Crop resistance plays a role in preventing aphid damage, benefiting food production industries, but its effects are limited due to aphid adaptation and phenotypic plasticity. Therefore, furthering understanding of aphid–crop interactions will improve our ability to protect crops from aphids. To determine how aphids adapt to resistant varieties of wheat, Triticum aestivum L. over time, we performed a laboratory experiment to assess the multi-generational effects of three wheat varieties, Batis, Ww2730, and Xiaoyan22, with different resistance levels on the fitness of Sitobion avenae (Fab.) (Hemiptera: Aphididae). The results showed that Ww2730 and Xiaoyan22 were more resistant than Batis to S. avenae, regardless of whether the aphids were newly introduced or had been acclimated before being introduced to the three wheat varieties. However, the effect of resistance on aphid life-history traits was time dependent. Aphid weigh gain increased and they development faster of the acclimated generation compared to the newly introduced generation on all three varieties. And the fecundity on the three varieties and net reproduction rates on Batis and Xiaoyan22 significantly decreased. Aphid fitness in terms of individual life-history parameters improved, whereas aphid fitness in terms of reproductive decreased, and a convergence effect, the difference gaps and standard errors of all life-history traits among the three acclimated populations had narrowed and were less than those in the three first-generation populations, was observed during the 3-mo experimental period. We suggested that S. avenae could rapidly respond to wheat resistance through life-history plasticity.